2002
DOI: 10.1179/026708401225005368
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Laser Alloying of A356 Al Alloy - Tribological Performance and Characterisation

Abstract: In the present work, sand cast Al alloy A356 was laser alloyed with tungsten using a two stage technique of laser alloying. A continuous wave, fibre optically delivered, Nd-YAG laser was employed for alloying the tungsten powder, and the coatings were produced by varying beam interaction with the substrate by altering the traverse laser velocity. Characterisation of the laser treated alloy was performed by various techniques. Optical (OM) and scanning electron microscopy (SEM) were used to examine the morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It was observed that the strengthened A356 alloy possessed a dry sliding wear resistance preferred to the plain A356 alloy. In Staia et al [31], the laser alloying of sand cast Al alloy A356 together with tungsten employing a two-phase method of laser alloying was performed. The conclusion was that the laser treated surfaces offered a growth in wear confrontation between 40% as well as almost 110% when weighed against the wear confrontation of the untreated Al alloy, as well as the enhancement was comparative to the laser beam-substrate interaction time.…”
Section: Literature Review 21 Extant Literature Review Concerning A3mentioning
confidence: 99%
“…It was observed that the strengthened A356 alloy possessed a dry sliding wear resistance preferred to the plain A356 alloy. In Staia et al [31], the laser alloying of sand cast Al alloy A356 together with tungsten employing a two-phase method of laser alloying was performed. The conclusion was that the laser treated surfaces offered a growth in wear confrontation between 40% as well as almost 110% when weighed against the wear confrontation of the untreated Al alloy, as well as the enhancement was comparative to the laser beam-substrate interaction time.…”
Section: Literature Review 21 Extant Literature Review Concerning A3mentioning
confidence: 99%